A randomised controlled study on the use of finishing and polishing systems on different resin composites using 3D contact optical profilometry and scanning electron microscopy. (April 2018) - Daud, Alaa; Gray, Gordon; Lynch, Christopher D.; Wilson, Nairn H.F.; Blum, Igor R.
Abstract: Objectives: The aim of this study was to evaluate theeffects of different finishing and polishing techniques on the surface roughness of microhybrid and nanofilled resin composites. Methods: The resin composites included were Filtek Z250 (a universal microhybrid resin composite) and Filtek Supreme XTE (a universal nanofill resin composite). Ninety cylindrical-shaped specimens were prepared for each composite resin material. The polishing methods used included tungsten carbide bur (TC); diamond bur (Db); Sof-Lex discs (S); Enhance PoGo discs (PG); TC + S; Db + S; TC + PG; Db + PG. Polymerisation against a Mylar strip without finishing and polishing acted as the control group. Surface roughness was measured using a 3D contact optical profilometer and surface morphology was examined by scanning electron microscope examination. Results: The results showed that the Mylar-formed surfaces were smoothest for both composites. Finishing with the 20 μm diamond finishing bur caused significantly greater surface irregularity (P < 0.0001) and damage than finishing with the tungsten carbide finishing bur. The Enhance PoGo polishing system produced smoother surfaces than the Sof-Lex disc polishing system; this difference was statistically highly significant (P < 0.0001). Conclusion: For both composites, the Mylar-formed surfaces were smoothest. Where indicated clinically, finishing is better conducted using a tungsten carbide bur- rather than a diamond finishing bur. The Enhance PoGo system was found to produce a smoother surface finish than the Sof-Lex system. Clinical significance: If finishing and polishing is required the use a tungsten carbide finishing bur followed by Enhance PoGo polishing may be found to result in the smoothest surface finish.